Analisis Pengaruh Faktor Internal dan Faktor Eksternal Terhadap Non Performing Financing pada Bank Umum Syariah - Framesa Januari Rahmah; Leni Nur Pratami; Iwan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Islamic banking at the moment is one of the most important things in the economy in Indonesia. Non Performing Financing (NPF) is one of the ratio that is considered by Islamic banking. NPF is an indicator that shows the risk of payment failure in the financing provided by Islamic banking. This study aims to analyze the influence of internal factors and external factors on Non-Performing Financing. The study was conducted at Islamic Commercial Banks in Indonesia for the 2014-2018 period. The internal variables used are the Capital Adequacy Ratio (CAR) and the Financing to Deposit Ratio (FDR) and the external variables used are the inflation rate, Gross Domestic Product (GDP) and the BI Rate. The results of the research shown by the t test show that partially the CAR and BI Rate variables have a negative effect on NPF meanwhile FDR, inflation and GDP variables have no effect on NPF.